Generalized height-diameter and crown diameter prediction models for cork oak forests in Spain - Sánchez-González, M.; Cañellas, I.; Montero, G. (Investigación Agraria: Sistemas y Recursos Forestales, 2007)
A generalized height-diameter equation, along with a crown diameter prediction equation for cork oak forests in Spain were developed based on data from the Second Spanish Forest Inventory. Nine generalised height-diameter equations were selected as candidate functions to model the height-diameter under cork relationship, while for the crown diameter prediction model five linear and non-linear equations were tested. The equations were fitted using the mixedeffects model approach. The Stoffels & Van Soest power equation, constrained to pass through the point of dominant diameter and dominant height, was selected as the generalised height-diameter model. Regarding the crown diameter prediction model, the parable function without the intercept and with quadratic mean diameter incorporated as a fixed effect into the b parameter, proved to be the model with best prediction capabilities. The models were validated by characterising the model error using the PRESS (Prediction Sum of Squares) statistic. Both equations will be submodels of the ALCORNOQUE v1.0, a management oriented growth and yield model for cork oak forests in Spain.
Keywords: crown width; forest growth modelling; height-diameter relationship; mixed effects models; Quercus suber